Intravenous Oxytocin Dosing Regimens for Postpartum Hemorrhage Prevention Following Cesarean Delivery: A Systematic Review and Meta-Analysis. Issue 2 (24th June 2022) - Phung, L.C.; Farrington, E.K.; Connolly, M.; Wilson, A.N.; Carvalho, B.; Homer, C.S.E.; Vogel, J.P.
Abstract : ( Am J Obstet Gynecol . 2021;225:250.e1–250.e38. [Epub May 4, 2021]) Postpartum hemorrhage (PPH) is a leading cause of maternal mortality. A common cause of PPH is uterine atony. To decrease the nearly 20% of 295, 000 worldwide maternal deaths from PPH, there has been an increase in the use of uterotonics for all women during delivery. In 2018 the World Health Organization (WHO) recommended 10 IU of oxytocin to be administered to all women for both vaginal and cesarean deliveries (CD) to improve uterine atony and prevent PPH. There is insufficient evidence that 10 IU was an optimal amount for both types of delivery and the dose was based on insufficient evidence from an outdated Cochrane systematic review. The purpose of this review was to analyze the dosing regimens of IV oxytocin used for CD and to determine if any regimens are superior to others.